Valuation and Application of Metaverse to CRM for B2B Sales in the Manufacturing Industry - NAKAJIMA, RYOSUKE (Digital Repository of Theses, 2024)
Throughout this research, the valuation and application of Metaverse service to CRM for the B2B Sales market in the manufacturing industry are executed to clarify the Problem Statement “How can we develop Metaverse services/products to CRM for B2B Sales market in the manufacturing industry?”. As the Research Methodology, Survey, Interview, and Proof of Concept (PoC) are executed. There are 22 questions in the research survey, and 540 respondents answered to this research survey. Then, interviews were conducted with 5 B2B marketing or sales representatives in the manufacturing industry. Lastly, the Proof of Concept (PoC) was executed with CROSSCO Co., Ltd, which is a Metaverse EXPO/Tradeshow vendor, to prepare Prototypes of B2B Metaverse EXPO as a trial and execute User Trial with 5 participants who joined in the interview sessions of this research. In conclusion, the following are the key elements to develop Metaverse services/products to CRM for the B2B Sales market in the manufacturing industry. • Key Industries: Manufacturing Machinery, Industrial Machinery, Electronics, Food & Beverages, Medical, Factory Automation, and Automotive industries • Key Technology: Augmented Reality (AR), Mixed Reality (MR), and Virtual Reality (VR) • Marketing Field: B2B enterprises in the manufacturing industry will effectively generate prospects/leads through EXPO/Tradeshow in the metaverse, including AR, MR, and VR. • Sales Field: Metaverse is practical and beneficial for promoting sales activity. Showing how the product/service works through AR or MR as a product demonstration is effective in the B2B industry. Also, the following are how to overcome the barriers. • Technical Barrier: If an employee can access the Metaverse environment via the Internet (without using VR goggles), it would not be a big difference from the current working environment. • Privacy/Security Issue: Based on the current technology, Metaverse platform providers protect the integrity of the virtual world and users by user authentication, data encryption, and access control to ensure that only authorized users can access the virtual world and its data. • High Development Cost: Based on current technology, Metaverse service is provided as pay-as-you-go without high initial costs. Also, if Metaverse is provided online/on the Internet without VR goggles, companies can reduce costs to start using Metaverse.